2009
DOI: 10.1016/j.jfms.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The Seizuring Cat

Abstract: Compared with the canine counterpart, the literature regarding treatment of feline seizures is less established. Recent clinical trials and studies are focusing on new treatment options for feline seizures. Specifically, these studies, some of which are ongoing, have led to the use of levetiracetam, zonisamide and pregabalin as add-on antiepileptics in cases that are refractory to phenobarbital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 33 publications
1
92
0
Order By: Relevance
“…It is reported that all cats with seizures have structural brain disease and as a result of this statement, it was believed for a long time that IE occurs only very rarely in cats . However, a considerable proportion of cats with recurrent seizures show no underlying disease , . In 3 larger retrospective studies, a total of 233 epileptic cats were evaluated and 77 (33%) classified as IE .…”
Section: Etiologic Classification For Catsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that all cats with seizures have structural brain disease and as a result of this statement, it was believed for a long time that IE occurs only very rarely in cats . However, a considerable proportion of cats with recurrent seizures show no underlying disease , . In 3 larger retrospective studies, a total of 233 epileptic cats were evaluated and 77 (33%) classified as IE .…”
Section: Etiologic Classification For Catsmentioning
confidence: 99%
“…However, focal epileptic seizures can become generalized so rapidly that their true nature is missed and the seizure might then be classified as primary generalized. The ictus usually lasts for not longer than 3 minutes …”
Section: Diagnostic Evaluation Of a Cat With Suspected Epileptic Seizurementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the etiology and diagnosis of epilepsy show similarities between dogs and cats, treatment with antiepileptic drugs (AEDs) in cats is different than in dogs [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Along with non-fatal adverse events like sedation, polyuria and polydipsia, diazepam has been linked to potentially fatal idiosyncratic hepatotoxicosis, hepatic necrosis and liver failure in cats [10]. Consequently, diazepam is often not considered a viable maintenance oral anticonvulsant option for cats [4, 11]. For the same reason other benzodiazepines like clorazepate are not recommended [12].…”
Section: Introductionmentioning
confidence: 99%